Vitamin D deficiency and maternal complications - Chandel, Anu B.; Mittal, Rita; Sharma, Anoop; Mittal, Shivika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Vitamin D deficiency is prevalent in India, a finding that is unexpected in a tropical country with abundant sunshine. Vitamin D deficiency is recognized as the most untreated nutritional deficiency currently in the world. Several studies reported the relationship between maternal vitamin D deficiency and adverse maternal and fetal outcomes including gestational diabetes, preeclampsia, preterm labour, low birth weight and increased rate of caesarean section. Methods: The study was conducted in the department of obstetrics and gynecology, Kamla Nehru Hospital, Shimla, Himachal Pradesh, India over a period of 12 months. Six hundred women were included in the study. Results: Forty-eight (8%) subjects developed preeclampsia-eclampsia syndrome, of which none had sufficient vitamin D levels, whereas 48 (100%) subjects had vitamin D deficiency. Conclusions: Maternal antenatal complications are more common in vitamin D deficient group.